Analisa Pemodelan Variasi Dinding Geser Ditinjau dari Waktu Getar Alami dan Simpangan antar Lantai pada Proyek Eco Green Church Malang - Haqq, Mohammad Ivan; Rochmah, Nurul (Politeknik Negeri Lhokseumawe, 2024)
The purpose of this research is to model 2 models with 2 defferent shear wall location. Shear wall is a concrete panel installed in the vertical direction of the building that serves to increase the structural strength of the building reduce displacement and distribute lateral shear forces on thr building due to earthquakes. The structural analysis uses SAP2000 v.22 software, as a tool and refers to SNI 1727-2019 and SNI 1726-2019; the results of the research from the 2 modeling, show that the mode shape that occurs from both modeling is tranlational in mode 1 and 2, the avarage deviation value obtained is 0,15889 mm in the X, direction and 0,1912 for the y direction and for avarage percentage is 0,2536 for the X direction while for the y direction it is 0,1245. The amount of mass participation that occurs is above 90% and in accordance with the requirement specified by SNI